Effect of hyaluronic acid on the struvite crystallization: A structural, morphological, and thermal analysis study - POLAT, SEVGİ (My University, 2022)
The struvite crystals constitute one of the common types of urinary stones. Such stones are also referred as \"infection stones\" due to their tendency to cause infections in urinary tract. A considerable effort has been placed to identify natural or synthetic crystal-growth modifiers for this kind of urinary stone in literature, yet macromolecules commonly found in urine have been underexplored. In the present study, we experimentally focus on how hyaluronic acid, a protein commonly found in urine, alters the struvite crystallization in aqueous solution and in an artificial urine media. By gradually adding ammonium dihydrogen phosphate to a solution containing magnesium chloride hexahydrate, reactive crystallization is carried out in a well-mixed and thermostated vessel at 37 degrees C. The resulting struvite crystals are characterized structurally by XRD and FTIR as well as morphologically and in terms of their surface charge. In addition, the thermal decomposition behavior of the struvite with and without hyaluronic acid and released volatile products were simultaneously investigated using a TGA/FTIR system. The average activation energy calculated using the Friedman method was 49.2 +/- 5.1 kJ/mol. The results of the kinetic and thermodynamic analyses showed that decomposition of the struvite crystals was endothermic and followed the multiple stage reaction mechanism.
Keywords: Kimya Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, CHEMICAL; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences; Struvite; crystallization; shape parameters; TGA/FTIR; thermal kinetics; ARTIFICIAL URINE; GREEN TEA; CRYSTALS; GROWTH; INHIBITION; STONES; DECOMPOSITION; MAGNESIUM; TRANSITION; KINETICS